Digital benefits among Early Childhood Education Lecturers (ECE) through New Pedagogies for Deep Learning (NPDL) through Teaching and Learning(TnL): Pemanfaatan digital dalam kalangan Pensyarah Pendidikan Awal Kanak (PAKK) melalui Kapasiti Pedagogi Pembelajaran Bermakna (KPPB) dalam Pengajaran dan Pembelajaran (PdP) - Abu Samah, Siti Iwana Sharizah; Kamaludin, Razila Aw; Harun, Luqman Hakim (Jurnal Pendidikan Bitara UPSI, 2022)
The success of a transformation agenda is based on the support from all levels of the organization and commitment to change. Utilization of digital through Teaching and Learning (TnL) among Early Childhood Education (ECE) lecturers in terms of knowledge and skills are dependent on the implementation of meaningful learning in line with the framework of the New Pedagogies for Deep Learning (NPDL). This study of the Institute of Teacher Education Malaysia (ITEM) aims to identify the level of knowledge of ECE lecturers in implementing Deep Learning through the use of digital in TnL. This study uses a survey method with 100 ECE lecturers from 24 Campus of Institutes Teacher Education (ITE) as a sample of the study administered online. Meanwhile, the data collection process was implemented using a questionnaire instrument consisting of the dimensions of the School Transformation Concept (TS25) which is 15 items of pedagogical capacity, 8 items of digital utilization, and 6 items of global competence. The analysis of the study showed that only 37.0% of the lecturers had reached a high level. Meanwhile, 45.0% of the people were at the moderate level and 18.0% at the low level. This indicates the need for digital utilization knowledge among ECE lecturers that needs to be improved. Based on these findings, four dimensions and three levels of competencies have been produced which contain 50 types of NPDL Competency Profiles. Therefore, to ensure the level of knowledge and competence of ECE lecturers is high on the latest pedagogy, emphasis on the need for digital utilization among ECE lecturers through meaningful learning pedagogical capacity in teaching and learning should be given priority. This is to ensure that the Institute of Teacher Education (ITE) is a leading center of excellence for world-class teacher training in producing competent teachers.